A simple parameterization for tsunami run-up prediction - Latifatul Cholifah; Tjipto Prastowo (Journal of Science and Science Education, 2017)
The linear shallow-water approximation is commonly used to describe tsunami propagation, where the wave is assumed as a long surface gravity wave. The evolution of wave height during its propagation from offshore to onshore is a classic problem. When arriving at a shoreline, the increased wave height causes severe destruction on infrastructures and fatalities. This problem has then been an important issue within the context of disaster risk reduction as it gives rise to the importance of tsunami run-up prediction. Using maximum run-up data from past events, we tested the applicability of the Green’s law based on shoaling only to calculate run-ups and found that the basic Green’s law was in doubt. Then, we examined energy density conservation involving refraction effect but no dissipation and derived a simple formula for parameterizing run-up height. Detailed descriptions on factors affecting run-ups, such as complex bathymetry and topography are not yet considered in the current study. The aim of this study is therefore to determine whether the modified Green’s law is applicable for tsunami run-up prediction using local water depths as external parameters and ray spacing widths in the normal direction of wave fronts related to refraction. The results are consistent with the measured run-ups, where approximately 70% of total points of observations confirm the modified Green’s law with a reasonable accuracy.